VIRTUAL SCREENING OF INDONESIAN HERBAL DATABASE FOR DNA METHYLTRANSFERASE INHIBITORS - WILAPUTRAKA, I GUSTI NGURAH RAKA BHASKARA; Azminah, Azminah; Erlina, Linda; Syahdi, Rezi Riadhi; Yanuar, Arry (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: DNA hypermethylation is an abnormal epigenetic process catalyzed by DNA methyltransferase 1 (DNMT1). It is also one of the factors that cause non-communicable diseases such as cancer, diabetes, and other metabolic diseases. DNA hypermethylation can be reversed by suppressing DNMT1 activity using a DNMT inhibitor. This study was conducted to seek out inhibitor candidates among natural products. Methods: The search for potential inhibitors was conducted through a virtual screening of the Indonesian Herbal Database using AutoDockVina as docking software. Twenty-five compounds known for their inhibitory activity against DNMT1 were used as actives and as a reference for generating decoys, which was done using the Directory of Useful Decoys, Enhanced. Results: The 12 compounds with binding energies below the cutoff value were cassiamin C (A1), procyanidin B2 (B2), ent-epicatechin- (4alpha->8)-ent-epicatechin (C3), epicatechin-(4beta->8)-epicatechin-3-O-gallate (D4), neorhusflavanone (E5), 3-O-galloylepicatechin- (4beta->6)-epicatechin-3-O-gallate (F6), withanolide (G7), 3-O-galloylepigallocatechin-(4beta->6)-epigallocatechin-3-O-gallate (H8), cyanidin 3-(6''-caffeylsophoroside)-5-glucoside (I9), epifriedelanol (J10), gallocatechin-(4alpha->8)-epicatechin (K11), and scutellarein 7-glucosyl-(1->4)- rhamnoside (L12). A1 had the lowest binding energy of −12.7 kcal/mol, whereas K11 had the highest of −11.5 kcal/mol. Conclusions: The virtual screening yielded five potential DNMT1 inhibitors: Procyanidin B2, ent-epicatechin-(4alpha->8)-ent-epicatechin, epicatechin-(4beta->8)-epicatechin-3-O-gallate, neorhusflavanone, and cyanidin 3-(6''-caffeylsophoroside)-5-glucoside.